Distant cutaneous metastasis from carcinoma of the uterus. A case report - Mandrekas, D.P.; Dimopoulos, A.M.; Moulopoulou, D.; Papamichalis, G.; Gougoulakis, A.G. (European Journal of Gynaecological Oncology, 1999)
Cutaneous metastasis from intraabdominal carcinoma is relatively rare. When it is present it is usually located in the skin overlying the neoplasm. Carcinoma of the uterus metastatic to the skin accounts for 9% of all cutaneous metastases. Distant metastasis is extremely rare. Such a metastasis to the skin of the big toe of the lower limb is presented.
Keywords: Endometrial carcinoma; Metastasis; skin cancer